Satisfaction Level of Rheumatoid Arthritis Patients Enrolled in the Treatment with Subcutaneous Tocilizumab - Filip Gucev; Lj Damjanovska-Krstikj; Dubravka Antova; Bashim Osmani; Mimoza Nikolovska Kotevska; Anzelika Karadzova Stojanovska; Sonja Pavlova; Emilija Sandevska; Maja Bojadjioska; Sonja Vidinik; N.G. Jordanovska; I Kafedjiska; et al. (Synergy Publishers, 2020)
Abstract: Background: The introduction of biological-Disease Modifying Agents (bDMARDs) has allowed serious improvement in the treatment of patients with rheumatoid arthritis (RA) by providing a better quality of life (QoL). Such improvements have been shown in patients using subcutaneous form of Tocilizumab SC (TCZ-SC), a humanized monoclonal antibody against IL-6 receptor. Objective: To assess the subcutaneous treatment satisfaction level and to evaluate the epidemiological profile of RA patients treated with TCZ-SC in North Macedonian Patients with RA. Methods: An observational study was conducted at the University Rheumatology Clinic in Skopje between October 1st and December 15th 2018, including 48 patients who have received TCZ-SC. In order to obtain patient’s satisfaction level and to evaluate the epidemiological characteristics of the patients, a standardized questionnaire was developed. Results: The mean age of the patient’s cohort was 50.9 years and 88.5% of the patients were females. More than half of the patients (58%) had high disease activity with mean disease duration of 5.35 years. Eighty three percent of the patients were entitled to receive subcutaneous TCZ because of the insufficient efficacy of previous treatment, All patients enrolled in the treatment with TCZ-SC, reported to be satisfied or very satisfied with the subcutaneous application of TCZ. They were also very satisfied with the previous education and the opportunity to receive the treatment at home. Conclusions: Tocilizumab as an efficient and well tolerated bDMARD is becoming a standard of care in the treatment of patients suffering from RA, offering unprecedented benefits for QoL improvement and satisfying the patients’ needs for modern and effective treatment.
Keywords: Rheumatoid arthritis; Tocilizumab-subcutaneous; Tocilizumab intravenous; treatment satisfaction level; patient’s preferences; epidemiological characteristics